The Nag Hammadi Library after Fifty Years : Proceedings of the 1995 Society of Biblical Literature Commemoration - Turner, Richard,; McGuire, Margaret Sönser, (Nag Hammadi and Manichaean Studies ;, 1997)
This volume contains 22 papers originally delivered at the Society of Biblical Literature's 1995 commemoration of the 50th anniversary of the discovery of the Nag Hammadi Library. Of these papers, five focus on the theme "Past, Present, and Future Research on the Nag Hammadi Codices" (J.M. Robinson, S. Emmel, B.A. Pearson, H.-M. Schenke, E.M. Yamauchi); thirteen stem from three seminars respectively devoted to the Apocryphon of John (M. Waldstein, F. Wisse, K.L. King, and S. LaPorta), the Gospel of Thomas and the Thomasine tradition (P.-H. Poirier, P.H. Sellew, J.-M. Sevrin, I. Dunderberg, S.R. Johnson, A. DeConick), and the Gospel of Philip ( E. Pagels, E. Thomassen, M. Turner); and two deal with the Valentinian school (C. Markschies, L. Painchaud & T. Janz).